On relative clauses and prosodic phrasing in Ciwandya - Mtenje, Al (ZAS Papers in Linguistics, 2011)
The interaction between Syntax and Phonology has been one area of interesting empirical research and theoretical debate in recent years, particularly the question of the extent to which syntactic structure influences phonological phrasing. It has generally been observed that the edges of the major syntactic constituents (XPs) tend to coincide with prosodic phrase boundaries thus resulting in XPs like subject NPs, object NPs, Topic NPs, VPs etc. forming separate phonological phrases. Within Optimality Theoretic (OT) accounts, this fact has been attributed to a number of well-motivated general alignment constraints. Studies on relative clauses in Bantu and other languages have significantly contributed to this area of research inquiry where a number of parametric variations have been observed with regard to prosodic phrasing. In some languages, XPs which are heads of relatives form separate phonological phrases while in others they phrase with the relative clauses. This paper makes a contribution to this topic by discussing the phrasing of relatives in Ciwandya (a Bantu language spoken in Malawi and Tanzania). It shows that XPs which are heads of restrictive relative clauses phrase with their relative verbs, regardless of whether they are subjects, objects or other adjuncts. A variety of syntactic constructions are used to illustrate this fact. The discussion also confirms what has been generally observed in other Bantu languages concerning restrictive relatives with clefts and non-restrictive relative clauses. In both cases, the heads of the relatives phrase separately. The paper adopts an OT analysis which has been well articulated and defended in Cheng & Downing (2007, 2010, to appear) Downing & Mtenje (2010, 2011) to account for these phenomena in Ciwandya.